Injury and pregnancy - London, P.S. (Injury, 1974)
This subject receives very little attention in textbooks and most of the articles in journals report small numbers of injuries of one kind or another. One general review suggests that between 5 and 10 per cent of pregnant women suffer injury, usually with no risk to the pregnancy: for example, the incidence of abortion ascribed to accidental injury is less than 1 in 10,000. Personal and reported experience can be summarized as follows. The baby may be injured during pregnancy or during birth, or may be harmed by the effects or complications of injury to the mother, e.g. Gram-negative septicaemia or hypoxic states. Injuries inflicted on the baby during pregnancy are most often fractures, which affect the skull almost as often as any other bone, and frequently accompany fractures of the mother's pelvis. Gunshot and other penetrating injuries of the child are rare and are not always fatal. Fractures of the maternal pelvis are the most frequent of the major injuries and are serious to viscera and other parts of the body. In some patients deformation of the pelvis can be corrected or prevented by operation, but it is usually best accepted. Rigid internal fixation of fractures of the lower limbs sustained in the later months of pregnancy can make labour much easier for the patient and her attendants. If the effect of injury on pregnancy is usually obvious, the effect of pregnancy on recovery from injury is usually not.